Persistent pulmonary hypertension of the newborn: recent advances in pathophysiology and treatment - Joaquim E.B. Cabral; Jaques Belik (Elsevier, 2013)
Objectives: Although recognized for decades, little is known about the etiology, physiopathology, and prevention of persistent pulmonary hypertension of the newborn (PPHN), and its treatment remains a major challenge for neonatologists. In this review, the clinical features and physiopathology of the syndrome will be addressed, as well as its general and specific treatments. Data source: A review was carried out in PubMed, Cochrane Library, and MRei consult databases, searching for articles related to the syndrome and published between 1995 and 2011. Data synthesis: Risk factors and the physiopathological mechanisms of the syndrome are discussed. The clinical presentation depends on the different factors involved. These are related to the etiology and physiopathology of the different forms of the disease. In addition to the measures used to allow for the decrease in pulmonary vascular resistance after birth, in some instances pulmonary vasodilators will be required. Although inhaled nitric oxide has proved effective, other vasodilators have been recently used, but clinical evidence is still lacking to demonstrate their benefits in the treatment of PPHN. Conclusions: Despite recent technological advances and new physiopathological knowledge of this disease, mortality associated with PPHN remains at 10%. More clinical research and evidence-based experimental results are needed to prevent, treat, and reduce the morbidity/mortality associated with this neonatal syndrome. Resumo: Objetivos: Embora reconhecida há décadas, ainda pouco se sabe a respeito da etiologia, fisiopatologia e prevenção da hipertensão pulmonar persistente neonatal (HPPN), e seu tratamento continua a ser um grande desafio para os neonatologistas. Nesta revisão, vamos abordar as características clínicas e os mecanismos fisiopatológicos da síndrome, assim como seu tratamento geral e específico. Fontes de dados: Fizemos uma revisão nas bases de dados PubMed, Cochrane Library e MRei Consult, procurando por artigos relacionados à síndrome e publicados entre 1995e 2011. Síntese de dados: São discutidos os fatores de risco e os mecanismos fisiopatológicos da síndrome. O quadro clínico depende dos diferentes fatores envolvidos, que provavelmente estão relacionados com a etiologia e o mecanismo fisiopatológico. Além das medidas utilizadas para permitir a queda da resistência vascular pulmonar após o nascimento, alguns casos necessitam de vasodilatadores pulmonares. Embora o óxido nítrico tenha se provado efetivo, recentemente, outros vasodilatadores têm sido usados, mas ainda faltam evidências clínicas para comprovar seus benefícios no tratamento da HPPN. Conclusões: Apesar dos recentes avanços tecnológicos e dos novos conhecimentos fisiopatológicos, a mortalidade associada à HPPN ainda é de 10%. São necessárias mais pesquisas clínicas e resultados experimentais baseados em evidências para prevenir, tratar e reduzir a morbimortalidade associada a esta síndrome neonatal. Keywords: Pulmonary hypertension, Pulmonary vasodilators, Nitric oxide, Palavras-chave: Hipertensão pulmonar, Vasodilatadores pulmonares, Óxido nítrico